The Role Of Digital Technology To Enhance Creativity And Innovation Skills For Learners In The 21st Century Era - Orbanus Naharia; Mozes Wullur; Norma Modigir (Eduvest - Journal of Universal Studies, 2024)
The 21st century era is characterized by the rapid advancement of digital technology that affects various aspects of life, including education. Digital technology offers various opportunities to improve the quality of education, including in developing creativity and innovation skills for learners. The purpose of this study is to explore and understand the role of digital technology in improving creativity and innovation skills for learners in the 21st century era. This research utilizes qualitative research with data collection techniques in the form of literature studies. After the data is collected, the analysis is carried out through 3 steps, namely data reduction, data presentation, then a conclusion is drawn. The findings of this study show that digital technology has an important role in improving creativity and innovation skills for learners in the 21st century era. Digital technology can help learners to develop creative thinking, improve problem solving skills, and develop adaptability. Strategies to integrate digital technology in learning to improve creativity and innovation skills for learners include creating a conducive learning environment for the use of digital technology, providing training to teachers on the use of digital technology, and developing digital technology-based learning resources.